Un estudio de los fondos de la biblioteca Francisco de Zabálburu. Los Impresos - Llera Llorente, Mª Teresa (Revista General de Información y Documentación, 2007)
The current article pretends to present one of Spain´s most important library collections, unknown by a lot of book lovers. This is the second part of a reseach which analyces printed material in our library.
Keywords: Bibliophilism; Old book; Collecting; Printed documents